Evaluation of Immunization Coverage in the Rural Area of Peshawar, Khyber Pakhtunkhwa - Khan, Adnan (Cureus, 2019)
Background: In children, the leading cause of morbidity and mortality is infectious disease. Immunization is one of the most cost-effective methods for child survival. The purpose of the survey is to assess access and coverage of immunizations in the rural areas of the District Peshawar, Khyber Pakhtunkhwa. Methods: A cross‑sectional study was conducted in a rural population area of District Peshawar from February 2016 to April 2016 using the WHO’s 30 cluster sampling method for evaluation of immunization coverage. Results: A total of 390 children aged 12-23 months were included in the study. It was found that 67.94% of the children were fully immunized against vaccine-preventable diseases. Thirty percent of the children were partially immunized; the percentage of unimmunized children was 2.06%. Immunization cards were issued to and available with 58.8% of the subjects. The most common cause of partial immunization was a lack of information regarding vaccinations (27%). Immunization against measles was found to be low (67%). Those using private facilities were more likely to be completely immunized as compared to government facilities. Conclusions: Immunization coverage in our survey was 68%. Sustained efforts are required to achieve universal coverage of immunization. Significant interventions are required, especially in areas that are more rural and less educated.